Effect of ultrasonic scaling and air polishing on the surface roughness of polyetheretherketone (PEEK) materials - Demirci, Fatih; Erdem, Merve Birgealp; Tekin, Samet; Caliskan, Cevdet (Mosher & Linder, Inc, 2022)
Purpose: To evaluate the effects of ultrasonic scaling (US) and air polishing (AP) on four polyetheretherketone (PEEK) composites. Methods: One hundred-twenty 15 x 3 mm discs of PEEK specimens were divided into four groups (n=30): Unfilled PEEK(U-PEEK), carbon fiber-reinforced PEEK(CFR-PEEK), glass fiber-reinforced PEEK(GFR-PEEK), and ceramic-filled PEEK(CF-PEEK). Each group was further divided into three subgroups (n = 10): control, US, and AP. Profilometry and scanning electron microscopy were used to analyze and evaluate surface roughness (SR). Statistical analyses of the data obtained were conducted using Shapiro-Wilk, Welch, and Games-Howell tests. Results: When the SR values of the specimens with US cleaning were evaluated, a statistically significant difference was found between the groups (P< 0.05). When the SR values of the specimens with AP cleaning were analyzed, there was a statistically significant difference in the CF-PEEK group (P< 0.05), whereas the other groups were not significantly different (P> 0.05). More studies are needed on CFR-PEEK and GFR-PEEK materials offered as alternatives to CF-PEEK in dentistry.
Keywords: In-Vitro Evaluation; Restorative Materials; Bacterial Adhesion; Biofilm Formation; Topography; Root